The outside option channel of central bank asset purchase programs: A tale of two crises - Changhyun Lee (University of California, Department of Economics, 2024)
I suggest a new channel through which central bank asset purchase programs could have effects on asset prices: The outside option channel. After the global financial crisis, central banks have widened the variety of assets they can purchase. Secondary markets for the majority of the newly targeted assets are characterized by the OTC market structure with matching frictions and bargaining features. In bargaining, the central bank's asset purchase announcement could affect the outside option value of the asset seller by providing one more option of selling the asset to the central bank to the seller. The effect of the outside option channel materializes even without actual purchases by the central bank since once the asset seller is matched with the buyer, she would exploit the announcement to require a higher price in the bargaining but not actually sell the asset to the central bank. I show how the outside option channel could work through a two-period model and discuss its empirical relevance by comparing two episodes of the Fed's asset purchases during the global financial crisis and the COVID crisis.
Keywords: E50; E58; G12; 330; Unconventional monetary policy; OTC markets; Asset pricing